1992
DOI: 10.1007/bf00145334
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of resistance phenotypes and plasmid analysis in multi-resistant 0:12 Pseudomonas aeruginosa

Abstract: Antibiotic resistance phenotypes, plasmid content and ability of conjugal transfer of antibiotic resistance genes of 35 multi-resistant Pseudomonas aeruginosa strains were examined. The strains were isolated in 12 Greek hospitals and the majority of them (80%) belonged to serotype 0:12. The isolates were distributed to a variety of different antibiotic resistance phenotypes. Plasmid analysis showed that 10 isolates harboured plasmids ranging in size from 20 to 100 Mda. Among these strains, four carried plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
2
5
2
1
Order By: Relevance
“…The other values too are higher than those obtained by Plesiat et al [21] and by Tsakris et al [6]; they, however, also found bigger plasmids using different techniques.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The other values too are higher than those obtained by Plesiat et al [21] and by Tsakris et al [6]; they, however, also found bigger plasmids using different techniques.…”
Section: Discussioncontrasting
confidence: 51%
“…Pitt et al [20] and Tsakris et al [6] isolated a high percentage of 0:12 serotype multiresistant strains in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the rate of development of resistance of P. aeruginosa to new antibiotics is much faster than the rate of development of new antibiotics (Tsakris et al, 1992;Holder et al,, 1995;Bukowska et al, 1996).…”
Section: Results and Dicussionmentioning
confidence: 95%
“…Acquisition of mobile genetic elements is known to be the main mechanism for short term accumulation of resistance determinants in bacterial genomes (Yah et al, 2007a). Other studies have shown resistance to gentamicin, tobramycin and carbenicillin to be attributed to transferable plasmids (Tsakris et al, 1992). Glatman et al (2001) in Greece, found plasmids (100Mda in size) isolated from multidrug resistant Pseudomonas aeruginosa strains, which encode high-level resistance to gentamicin and tobramycin; whereas resistant to other drugs such as ciprofloxacin and rifampicin were not transferable and all.…”
Section: Discussionmentioning
confidence: 99%